A Program for Weaning Children from Enteral Feeding in a General Pediatric Unit: How, for Whom, and with What Results? - Mirete, Justine; Thouvenin, Béatrice; Malecot, Gaelle; Le-Gouëz, Morgane; Chalouhi, Christel; du Fraysseix, Catherine; Royer, Aurélie; Leon, Anais; Vachey, Clément; Abadie, Véronique (Frontiers in Pediatrics, 2018)
Objective To describe a series of children who were hospitalized for a tube-weaning program in the general pediatric ward of a pediatric tertiary university hospital: describe our method, to determine the success rate of our inpatient pediatric tube weaning program, and search for relevant factors linked to its success or failure. Method We analyzed the medical files of consecutive children who were hospitalized for gastric-tube weaning over an 8-year period. We analyzed outcomes in terms of feeding and growth with at least 2 years of data. Success (weaning within 3 months) and failure were compared by characteristics of children. Results We included 37 children (29 females) with mean (SD) age 31.4 (21) months. Most had a severe medical history (30% prematurity; 50% intrauterine growth restriction, 50% neurological and genetic anomalies). The weaning program was successful for half of the children. Factors linked to success of the program were female sex (p = 0.0188), normal neurodevelopment (p = 0.0016), nasogastric tube (p = 0.0098), and with <24 months on EF before the stay (p = 0.0309). Discussion Comparing the efficiency of various methods and results among teams was difficult, which indicates the need to establish consensus about the outcome criteria. We confirm the need for these types of stays and programs.